Financial Literacy and Retirement Readiness for Oil and Gas Indonesian Expatriates in Qatar - Fachrurazy, Sofwan (Pelopor Publikasi Akademika, 2023)
Expatriates are individuals who reside outside their country of origin. Their occupation is characterized as high-density, intricate, and more demanding than domestic work (Shin, 2007). In Qatar, expatriates have been employed in the oil and gas industry since 1940. However, in December 2015, Qatar Petroleum, like numerous other organizations in the oil and gas sector, encountered challenges during the period of 2015-2016 due to a sharp decline in global oil prices. The decline in oil prices during this period was primarily driven by a combination of factors, including oversupply in the global oil market, reduced demand, and geopolitical factors. These circumstances exerted significant financial pressure on many oil and gas companies worldwide, including Qatar Petroleum. To alleviate the financial impact of plummeting oil prices, many oil and gas companies had to implement cost-cutting measures, frequently involving layoffs and workforce reductions. These measures were taken to decrease operating expenses and maintain financial stability during low oil prices. In addition to this, Qatar 2008 introduced Vision 2030, which serves as a comprehensive and long-term development plan for the nation. This plan outlines Qatar's objectives and aspirations across various sectors, including economic, social, environmental, and cultural development, with a particular emphasis on sustainability and economic diversification. The leadership of Qatar presented this vision as a strategic roadmap for the country's progress over the next few decades, leading up to the year 2030. Considering these two initiatives, it is imperative for all expatriates, particularly Indonesian expatriates, to prepare for early retirement. According to the database of the Ikatan Ahli Teknik Perminyakan Indonesia (IATMI) commissariat in Qatar, there are currently over 1653 Indonesian expatriates employed in the oil industry. Research findings indicate that the financial literacy of expatriates, which refers to their knowledge, skills, and beliefs influencing decision-making and financial management to achieve prosperity, is relatively low at 46%. Furthermore, there is a weak correlation between financial literacy and preparedness for early retirement